High Prevalence of Secondary Resistance Mutations in Venezuelan HIV-1 Isolates - Dieudonne, Mariacarolina; Garzaro, Domingo; Torres, Jaime; Naranjo, Laura; Antonio Suárez, José; Castro, Julio; Martínez, Nahir; Castro, Erika; Berrueta, Lisbeth; Salmen, Siham; Devesa, Marisol; Rangel, Héctor R; et al. (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The genetic variability was studied in HIV-1 from Venezuelan patients with and without treatment, in order to evaluate the presence of polymorphisms and drug resistance mutations. Proviral DNA from peripheral blood mononuclear cells or viral RNA from plasma was extracted from the blood of 30 patients. Two regions from the polymerase gene, protease (Pr) and reverse transcriptase (RT) and one genomic fragment from the envelope (Env) gene were amplified and sequenced. All HIV-1 samples analyzed were classified as subtype B, without evidence of recombination. Although no primary protease mutations were detected, a high frequency of secondary mutations (86%, 19/22), associated to restoration of viral replicative fitness, was observed in strains circulating both in treated and non-treated patients. Resistance mutations to nucleoside RT inhibitors (NRTI) and non-nucleoside RT inhibitors (NNRTI) were detected in 35% (6/17) and 12% (2/17) of the viruses circulating in treated patients, respectively. Resistance mutations were also present in the virus infecting one antiretroviral na í¯ve individual (7.7%), suggesting that local screening for resistant mutation in na í¯ve patient might be important to minimize therapy failure. Future studies are warranted to assess the role of secondary mutation in the success of viral infection